O Ministério Público e o inquérito civil - Araújo, Fernando Henrique de Moraes (2007)
The scope of this paper is to analyze the performance of the Department of Justice ahead of the civil inquiry in the injunction of transindividual interests. It is a compilatory paper, in which a national and foreign doctrinaire standpoint is presented on the subject, as well as legislation and case law. The choice of the subject matter originated in the need to deepen the view about the performance of the Department of Justice towards the presidency of the exclusive investigation instrument for the defense of metaindividual interests: the civil inquiry. The existing relation between the civil enquiry and the instrumental view of the civil procedure, the historic origin of the metaindividual interests and the respective influence of the three most important periods to the development of the collective injunction in the world: the English medieval, the North American and the Italian. The target is the historic origin of the Department of Justice in the alien proceeding, subsequently focusing on the evolution of the institution in Brazil, with a standpoint more concentrated on the current organizational structure and the correlative constitutional principles. Then, the approach is the study of the civil enquiry, including the general aspects of the truly Brazilian investigation instrument. Finally, a brief view on the collective injunction in foreign proceeding is presented, paying special attention to the South American countries. Statistic data are enclosed presenting the use of the civil enquiry by the Departments of Justice of the Federal and State Governments, as well as the main proceduring regulations of the instrument in the respective Parquet structures